Molecular and epidemiological characterization of carbapenem-resistant hypervirulent Klebsiella pneumoniae in Huaian, China (2022–2024): a retrospective study - Lian, Jianchun; Li, Qianhui; Peng, Cheng; Lin, Tao; Du, Hong; Tang, Chaogui; Zhang, Xiaoyun (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesCarbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKP) poses a significant public health challenge. This study investigated the molecular epidemiology, antimicrobial resistance patterns, clinical characteristics, and risk factors of CR-hvKP infection in Huaian, China.MethodsWe retrospectively studied patients infected with carbapenem-resistant K. pneumoniae (CRKP) between November 2022 and September 2024. Whole-genome sequencing was used to detect carbapenemase, virulence, capsular serotype-related genes, and plasmid types in 374 CRKP isolates.ResultsAmong them, 57.49% (215/374) strains met the criteria for CR-hvKP. The most common type was blaKPC-2-producing ST11(98.60%, 212/215), whereas K64 (56.74%, 122/215) and KL25 (39.53%, 85/215) were the main capsular serotypes. The CR-hvKP strains showed significantly higher resistance to the tested antibiotics, except for ceftazidime/avibactam and colistin. Resistance rates of CR-hvKP to the three tested antibiotics (minocycline, cotrimoxazole, and amikacin) were higher than those of CRnon-hvKP. Phylogenetic analysis based on whole-genome single-nucleotide polymorphisms divided the 251 isolates into four independent branches, with branch 2 being the most prevalent, indicating high clonality among the strains. Multivariate analysis showed diabetes [odds ratio (OR) = 3.771] and surgery (OR =2.042) to be independent variables associated with CR-hvKP infection.ConclusionsNotably, the ST11 lineage carrying blaKPC-2 has emerged as a dominant high-risk clone in Huaian. Given the wide distribution of these novel CR-hvKP isolates, global monitoring and stricter control measures should be implemented to prevent their further spread in hospital settings.